PROSEDUR PENGUJIAN SUBSTANTIF ATAS AKUN UTANG USAHA PADA PT DIM OLEH KANTOR AKUNTAN PUBLIK PAUL HADIWINATA, HIDAJAT, ARSONO, RETNO, PALILINGAN, DAN REKAN - Shabrina Dinda Putri (2022)
Auditing is an examination that is carried out systematically and independently, on the financial statements that have been prepared by the company's management. Determining the level of materiality is one of the most important things in conducting an audit, so that the auditor decides the tolerable level of misstatement for significant accounts or classes of transactions. Substantive testing is a test in the audit that aims to analyze or examine the financial statements in detail contained in the accounts that can affect the fairness of PT DIM's financial statements. Substantive testing of accounts payable is aimed at finding a presentation of accounts payable that is lower than the amount it should be. Based on the substantive tests carried out, it can be concluded that the accounts payable of PT DIM in 2021 have been presented fairly and there are no material misstatements.